Evaluation of raw and processed Phellodendri Chinensis Cortex using the quality marker analysis strategy by UHPLC-Q-Orbitrap MS and multivariate statistical analysis - Wang, Wang; Shi, Xuqin; Zhu, Guoxue (Frontiers in Chemistry, 2023)
Phellodendri Chinensis Cortex is a necessary part of healthcare for its significant clinical efficacy.Raw and processed Phellodendri Chinensis Cortex is both documented in the Chinese Pharmacopoeia (2015). After processing, the therapeutic effects are believed to differ according to traditional Chinese medicine theories. However, the chemical mechanism responsible for this processing, according to traditional Chinese medicine theories, is still not clear. In this study, the therapeutic effects of various ions were examined based on traditional Chinese medicine theories using ultrahigh performance liquid chromatography-hybrid quadrupole-Orbitrap mass spectrometry (UHPLC-Q-Orbitrap MS) coupled with multivariate statistical analysis, such as principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA), to comprehensively compare the differences between raw and processed Phellodendri Chinensis Cortex for the first time. 48 compounds were screened out and ten of them simultaneously transformed with significant variation in processed products compared with raw materials. It was illustrated that the contents of berberine, palmatine, jatrorrhizine, magnoflorine, menisperine, phellodendrine, tetrahydrojatrorrhizine and tetrahydropalmatine decreased, while the compounds of berberrubine, fernloylquinic acid methyl ester were newly appeared in processed herbs. This is likely to be related to the conversion of ingredients during processing. Taken as a whole, the fact that quality markers have been successfully identified to differentiate processed Phellodendri Chinensis Cortex from raw materials suggests that this approach could be used for the investigation of the chemical transformation mechanisms involved in the processing of herbal medicine.